How naive realism can explain both the particularity and the generality of experience - French, Craig; Gomes, Anil (Wiley, 2019)
Visual experiences seem to exhibit phenomenological particularity: when you look at some object, it – that particular object – looks some way to you. But experiences exhibit generality too: when you look at a distinct but qualitatively identical object, things seem the same to you as they did in seeing the first object. Naïve realist accounts of visual experience have often been thought to have a problem with each of these observations. It has been claimed that naïve realist views cannot account for the generality of visual experiences, and that the naïve realist explanation of particularity has unacceptable implications for self- knowledge: the knowledge we have of the character of our own experiences. We argue in this paper that neither claim is correct: naïve realism can explain the generality of experiences, and the naïve realist explanation of particularity raises no problems for our self-knowledge.